Anatomi Keragaman Batang Gyrinops versteegii (Thymelaeaceae) di Pulau Sumbawa (Stem diversity of Gyrinops versteegii (Thymelaeaceae) in Sumbawa Island - Tri Mulyaningsih; Aida Muspiah; Zainul Muttaqin Sany (Fakultas Kehutanan Universitas Gadjah Mada, 2022)
The aim of this research is to determine the comparative anatomy of the stem of Gyrinops versteegii (Thymelaeaceae) in Sumbawa Island. Stem samples of G. versteegii were used from collections of the Agarwood Center Laboratory, Faculty of Mathematics and Natural Science, University of Mataram that were taken from Sumbawa Island. This research used permanent slides with freehand section and maceration methods. Observation data consisted of cortex tissues, xylem, pith, and Ca-Oxalate crystals. The results showed that there were four provenances of G. versteegii on Sumbawa Island, namely provenance Pantai, Hajumee, Kayuk Pisak, and new provenance (Tartar provenance). Comparison of anatomy between the stems of G. versteegii provenance Pantai with other provenances had differences in periderm thickness, the pattern of tissue sclerenchyma, interxylary phloem thickness, cortical parenchyma diameter, number of rows of wood parenchyma tissue, tracheid diameter, pith cell diameter, Ca-oxalate shape. Provenance Hajumee with Tartar and Kayuk pisak differed in trachea length, trachea diameter, and the length of the tracheids, while between the provenances of Tartar and Kayuk pisak differed in the frequency of the trachea, the length of the fiber tracheids, the arrangement of the pith radius, and the location of the pith.